Key findings and recommendations from the IMPACTS project. (November 2016) - Brunsvold, Amy; Jakobsen, Jana P.; Mazzetti, Marit J.; Skaugen, Geir; Hammer, Morten; Eickhoff, Charles; Neele, Filip
Highlights: High-quality vapour-liquid equilibrium data were acquired for CO2 -N2, CO2 -O2 and CO2 -Ar mixtures. A new reference equation of state EOS-GS has been developed for impure CO2 . The publicly available TREND software enables modelling the true behaviour of impure CO2 mixtures. New methodologies are suggested for selecting design criteria for safe operation of CO2 pipelines. New design methods may reduce power consumption on operation of pipelines. Abstract: The IMPACTS project investigated how impurities affect the design and operation of CO2 transport and storage processes. Experimental work and modelling have advanced the state of the art in the areas of how impurities in CO2 affect thermo-physical properties, fluid flow, corrosion, and reservoir chemical reactivity. High-quality experimental thermodynamic data were obtained to develop new reference equations of state for exhaust gases (EOS-CG). Parts of the results have been distributed as the publicly available TREND 2.0 software. The software enables modelling the true behaviour of impure CO2 mixtures, thereby increasing the fidelity of the simulations. IMPACTS also provided recommendations that relate results from parts of the CCS chain into results that relate to the entire CCS chain. They cover such areas as trade-offs between impurity levels and CCS system costs, optimized CO2 quality on a case-by-case basis for CCS chains, and design/operation of pipelines. New methodologies have been suggested for selecting the design criteria for operation of CO2 pipelines to avoid two-phase flow and running ductile fractures. This can help limit over-specifying design and reduce costs. For example, IMPACTS has shown how 4% of impurities in the CO2 can increase the power consumption for compression and processing by 50%. IMPACTS has generated a large amount of new knowledge and is an example of how a wide-reaching research program with several groups investigating different aspects of the same topic has brought the knowledge base forward while ensuring that the results are aligned.